APAKAH MANAJEMEN LABA TERMASUK KECURANGAN ? : ANALISIS LITERATUR - Kurniawansyah, Deddy (Universitas Airlangga, 2018)
Many maintain that earnings management is harmful. This literature study explains and describe the issue from the outside perspective of earnings management. This research method used qualitative with literature study. The results of this study are Earnings management is not a fraud. Fraud is an